SAT0457 SjÖgren big data project, the first example of data sharing in autoimmune diseases: analysis of 10475 worldwide patients. (12th June 2018) - Retamozo, S.; Acar-Denizli, N.; Fai Ng, W.; Zeher, M.; Rasmussen, A.; Mandl, T.; Seror, R.; Li, X.; Baldini, C.; Gottenberg, J.-E.; Danda, D.; Quartuccio, L.; et al.
Abstract : Objectives: To take a "high-definition" picture of the main features of primary Sjögren syndrome (SjS) following a worldwide data-sharing cooperative merging of international clinical SjS databases. Methods: The Big Data Sjögren Project Consortium is an international, multicentre registry created in 2014 including leading clinical centres in SjS of the 5 continents that shared a harmonised data architecture and conducted cooperative online efforts to refine collected data of primary SjS patients fulfilling the 2002 classification criteria. Results: By January 2018, the participant centres had included 10 475 patients from 22 countries, including 7637 (73%) patients from Europe, 1420 (14%) from America, 1186 (11%) from Asia, 167 (1.4%) from Australia and 65 (0.6%) from Africa. The cohort included 9781 (93%) women and 694 (7%) men, with a mean age at diagnosis of primary SjS of 53 years. The frequencies of fulfilment of the 2002 criteria were 92% for dry eye, 94% for dry mouth, 83% for abnormal ocular tests, 82% for positive minor salivary gland biopsy, 78% for abnormal oral diagnostic tests and 76% for positive anti-Ro/La antibodies. The frequency of positive immunological markers at diagnosis was 79% for ANA, 73% for anti-Ro, 49% for RF, 45% for anti-La, 13% for low C3 levels, 14% for low C4 levels and 7% for cryoglobulins. Conclusions: International data sharing-based projects merging disperse clinical registries may be essential tools to increase current knowledge and to improve patient care in specific systemic autoimmune diseases. Disclosure of Interest: None declared